SYSTEMATIC LITERATUR REVIEW: MODEL PROBLEM POSING TERHADAP KEMAMPUAN MATEMATIS - Azis, Nasya Maharani (UNIVERSITAS TANJUNGPURA, 2024)
Students' lack of mathematical ability can affect their low mathematics learning outcomes. By using Systematic Literature Review, a comprehensive and methodical analysis, it can be determined whether the Problem Posing learning model is an effective tool to optimize students' mathematical ability. 38 articles from 2020 to 2024 were collected and analyzed, consisting of 10 articles in elementary school, 16 articles in junior high school and 12 articles in high school. From the research results, it was found that the use of Problem Posing in mathematics learning is beneficial to mathematical abilities ranging from elementary to high school. The mathematical abilities that have been studied consist of creative thinking, mathematical reasoning, mathematical communication, critical thinking, mathematical understanding, problem solving, and logical thinking. Hopefully, this research can help educators and future researchers in choosing learning models in the classroom.Keywords: mathematical ability, Problem Posing model, Systematic Literature Review